IMPROVING COMMUNICATIONS IN PUBLIC ADMINISTRATION IN THE CONTEXT OF IMPLEMENTING ANTI-CORRUPTION POLICY - Sydorenko, Oleh; Panchenko, Hanna (Public Management and Policy, 2025)
Active digitalization processes and the development of technological innovations determine the need to transform the public administration system in the context of communication support. At the same time, an inevitable stage of the European integration development of management processes is seen as an increase in the level of information security and an effective fight against corruption. The purpose of the article is to determine the potential for the development of communication support in public administration in the context of the implementation of anti-corruption policy. The article analyzes theoretical approaches, identifies the main problems in communication between governmental structures and the public, and outlines the ways to solve them. The author proposes a unified model for improving communications, which takes into account modern digital tools, transparency of information and active participation of civil society. It is found that the key aspects of communication improvement of management processes are the provision of electronic information and the provision of e-services, as well as the improvement of the process of interaction between public administration, the business sector and the public. It is substantiated that the integration of modern information and communication solutions into the practical processes of public administration increases the efficiency and accuracy of management decisions, minimizes the threat of confidential data leakage, and promotes partnerships between all stakeholders in the public administration system. The study proves that the digitalization of the communication environment has a positive impact on the upgrade of public administration in the context of preventing corruption risks.